PEMANFAATAN HASIL EVALUASI PERKULIAHAN UNTUK PERBAlKAN MUTU PERGURUAN TINGGI - Wawan S. Suhennan (LPMPP Universitas Negeri Yogyakarta, 2003)
The purpose of this article is to describe argumentatively thefollow-up that needsto be done by university lecturers and theiruniversityof the result of students' evaluation of the lectures thathave been conducted.The evaluationof a university lecture is a decision-makingprocessof assessing the process and result of the lecture based oncollected facts and infonnation.It can be executed internally andexternally. University lecturers seldom makean evaluation of theirlecturesfor reasons of limited time and unavailability of any validinstrument. Even though evaluationof the lectures by students isalready a policy of the university, utilization of the result is notoptimumyet.The evaluation of such lectures should involve the studentsbecause they are the oneswho are to be the most concerned aboutthe resultsof the lecturing process and they already have enoughabilityto evaluate the process. Generally, questionnaires are theinstruments usedto collect the infonnation and data in evaluating thelectures. The resultofsuch evaluation is useful as feedback and basisfor making improvements, detennining the accountability, andmonitoring and controlling the qualityof education. As a follow-up,university lecturers and the university can adopt the followingagenda:(l) making decisions, (2) improving the quality of lecturesand conducting classroom action research,(3) establishing a standard for lecturing quality, and (4) establishing an assurance of theuniversity's quality